Enriched environment enhances transplanted subventricular zone stem cell migration and functional recovery after stroke - Rissanen, Anna; Hewlett, K.; Windle, V.; Chernenko, Garry A.; Ploughman, M.; Jolkkonen, Jukka; Weiss, S.; Corbett, Dale (My University, 2007)
Stroke patients suffer from severe impairments and significant effort is under way to develop therapies to improve functional recovery. Stem cells provide a promising form of therapy to replace neuronal circuits lost to injury. Indeed, previous studies have shown that a variety of stem cell types can provide some functional recovery in animal models of stroke. However, it is unlikely that replacement therapy alone will be sufficient to maximize recovery. The aim of the present study was to determine if rodent stem cell transplants combined with rehabilitation resulted in enhanced functional recovery after focal ischemia in rats. Middle cerebral artery occlusion was induced by injection of the vasoconstrictive peptide endothelin-1 adjacent to the middle cerebral artery. Seven days after stroke the rats received adult neural stem cell transplants isolated from mouse subventricular zone or vehicle injection and then subsequently were housed in enriched or standard conditions. The rats in the enriched housing also had access to running wheels once a week. Enriched housing and voluntary running exercise enhanced migration of transplanted stem cells toward the region of injury after stroke and there was a trend toward increased survival of stem cells. Enrichment also increased the number of endogenous progenitor cells in the subventricular zone of transplanted animals. Finally, functional recovery measured in the cylinder test was facilitated only when the stem cell transplants were combined with enrichment and running exercise 7 days after the transplant. These results suggest that the ability of transplanted stem cells in promoting recovery can be augmented by environmental factors such as rehabilitation.
Keywords: stroke; stem cell transplants; neuroplasticity; rehabilitation; cell replacement